Surgical management of sphenoid ridge meningioma en plaque (spheno-orbital meningioma) - Gasser Hasan Al-Shyal; Mohamed Soliman Mohamed; Mohammad Fathy Eissa (Wolters Kluwer Medknow Publications, 2020)
Background and aim The aim of the study was to investigate the surgical techniques to remove meningioma en plaque and to compare our technique and results with other authors. Patients and methods This retrospective series case was done at our University Hospital. Eight patients were managed at Al-Zahraa University Hospital between March 2016 and March 2018. Preoperative and postoperative clinical and radiological assessments were done for each patient. Results There were eight patients in our study. All patients are women. The age range was from 34 to 60 years and the mean was 45.4 years. Proptosis was the main clinical manifestation and it was present in all eight patients. Three (37.5%) patients had visual impairment while two (25%) of them had headache and retro-orbital pain. We achieved total resection in six (75%) out of our eight patients. All tumors were WHO grade 1 meningiomas. Regarding surgical outcome, proptosis improved in six (75%) of the eight cases. Visual impairment improved in two (66.7%) cases out of three who had visual declination preoperatively. Conclusion Meningioma en plaque can be safely removed without any morbidity or mortality. Proptosis and hyperostosis in the sphenoid bone are highly suggestive and this requires more accurate radiological studies. MRI with contrast is essential for these cases. Extensive bony drilling is required for gross total resection. It also facilitates resection of the soft part of the tumor with its dura. Some cases may need orbital wall reconstruction. Proptosis mostly improves after surgery.